2021
DOI: 10.1096/fj.202002025rr
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characteristics of lipid‐induced Aβ oligomers correlate to distinctive phenotypes in transgenic mice

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects cognition and memory. Recent advances have helped identify many clinical sub-types in AD. Mounting evidence point toward structural polymorphism among fibrillar aggregates of amyloid-β (Aβ) to being responsible for the phenotypes and clinical manifestations. In the emerging paradigm of polymorphism and prion-like propagation of aggregates in AD, the role of low molecular weight soluble oligomers, which are long known to be the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 75 publications
(110 reference statements)
0
24
0
Order By: Relevance
“…DMPC generated oligomers had a slightly higher cytotoxicity compared to LR and TBE (Figure 3e). Overall, these data suggest that LUVs with different surface properties and charge could lead to the generation of structurally distinctive neurotoxic oligomers as observed in micellar systems 22 .…”
Section: Aβ Oligomers Isolated From Gm1 Enriched Vesicles Show Distin...mentioning
confidence: 66%
“…DMPC generated oligomers had a slightly higher cytotoxicity compared to LR and TBE (Figure 3e). Overall, these data suggest that LUVs with different surface properties and charge could lead to the generation of structurally distinctive neurotoxic oligomers as observed in micellar systems 22 .…”
Section: Aβ Oligomers Isolated From Gm1 Enriched Vesicles Show Distin...mentioning
confidence: 66%
“…71 Studies have also shown that Aβ oligomers derived from fatty acids, micellar phospholipids, and GM1 build up the amyloid plaques in AD transgenic mice. 98,99 In 1993, Arispe et al 100 demonstrated that the synthetic Aβ peptide inserts into the artificial lipid bilayer and form cation-selective channels. One of the mechanisms of neurodegeneration caused by Aβ is through the amyloid pores formation.…”
Section: Cell Membrane-mediated Toxicitymentioning
confidence: 99%
“…Various neurodegenerative amyloid disorders like Parkinson's disease and AD have long been associated with increased cell permeability and increased intracellular concentration of calcium ions (Figure 3). 71 Studies have also shown that Aβ oligomers derived from fatty acids, micellar phospholipids, and GM1 build up the amyloid plaques in AD transgenic mice 98,99 . In 1993, Arispe et al 100 demonstrated that the synthetic Aβ peptide inserts into the artificial lipid bilayer and form cation‐selective channels.…”
Section: Mechanism Of Toxicity Mediated By Aβ Oligomersmentioning
confidence: 99%
“…Cell viability assay was carried out using 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino)carbonyl]-2H-tetrazolium hydroxide (XTT) in SH-SY5Y cells as described in our previously established protocols [40,43]. Briefly, human neuroblastoma SH-SY5Y were maintained at 37 °C with 5.5 % CO2 in DMEM: F12 (1:1) media containing 10% FBS and 1% penicillin/streptomycin.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…Circular dichroism (CD) spectra of respective samples were measured in 20 μM Tris buffer pH 8.0 in the far UV region in Jasco J-815 spectrophotometer (Jasco MD) using the established protocol [43].…”
Section: Circular Dichroismmentioning
confidence: 99%